(3JLGQH GdCee hJYGbH Gdgees - (3CMeO Hf eMeO Hf jYbhH perSncnhrjg, CHh Ydj,J (B421 (3g` s
(3ChdgG (B:s
(3HKbdI hCehGdg Edi cGHd TGg , heVi MJi fRd GdcQR , hYHOGdQMef Hf CSde jJHYg s
(3BNQgG (B:s
(3hgPG BNQ eG Yedg GdCSJGP CHhYdj CMeO Hf eMeO Hf jYbhH eSchjg s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B168s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B342 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B582 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B91 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs